A Modified Bioceramic Sealer with Dual Antibacterial Mechanisms - Bashayer Baras; Amal Almohaimede; Yara Alshibani; Farah Alzahrani; Raseel Alageel; Michael D. Weir; Hockin H. K. Xu (Bioengineering, 2025)
Continued efforts have been made to enhance the antibacterial properties of root canal sealers by adding antimicrobial agents to them. This study aims to investigate the antibacterial effect of 0.15% silver nanoparticles (NAg) and 5% dimethylaminohexadecyl methacrylate (DMAHDM) when added to EndoSequence Bioceramic (BC) sealer against Enterococcus faecalis (E. faecalis) biofilm and their impact on its physical properties (flowability and film thickness). Four root canal sealers were tested for flow and film thickness properties, as well as against antibiofilm of E. faecalis-impregnated dentin discs, as follows: group 1: EndoSequence BC sealer only; group 2: EndoSequence BC sealer + 0.15% NAg; group 3: EndoSequence BC sealer + 5% DMAHDM; and group 4: EndoSequence BC sealer + 0.15% NAg + 5% DMAHDM. The findings show that all groups had flow and film thickness values that were in accordance with the ISO requirements. Combining 0.15% NAg and 5% DMAHDM in EndoSequence significantly reduced colony-forming unit (CFU) counts by approximately 5 logs. The combination of NAg and DMAHDM offers a promising strategy for developing endodontic sealers with improved antimicrobial properties and acceptable physical performance.